PWE-396 Diagnostic laparoscopy and the outcome of macroscopically normal appendicectomy in female patients with right iliac fossa pain. (22nd June 2015) - Ghosh, A; Addison, A; Agrawal, A
Abstract : Introduction: Right iliac fossa pain (RIF) pain, caused by suspected acute appendicitis continues to prove diagnostically challenging with 15–30% of appendices removed being macroscopically normal. Diagnostic laparoscopy (DL) is being used as both diagnostic and therapeutic procedure particularly in female patients. The aim of this study was to assess the rate of macroscopically negative appendicectomies (MNA) and complications in a cohort of female patients who had DL for suspected appendicitis. Furthermore to follow up the re-admissions rates in those who did not have appendicectomy in the absence of positive findings. Method: A retrospective study of consecutive female patients admitted with acute abdominal pain that underwent DL for suspected acute appendicitis with an 18-month follow-up. An electronic structured proforma was used to collect data related to white cell count (WCC), C-reactive protein (CRP), ultrasonography (US), operative findings, histology, morbidity and mortality were collated. Results: In total of the 159 patients were included in the study (mean age 30; 16–76). On admission 118 patients (74%) had a raised WCC (>11), of which 84% (91/119) had a raised CRP (>10). 48 patients underwent US, with 26 having a radiological diagnosis of appendicitis prior to laparoscopy. 146 patients underwent laparoscopic appendicectomy. At laparoscopy 120 patients had a macroscopic diagnosis of acute appendicitis, while 26 of the patients that underwent appendicectomy had MNA, although there was a decision to proceed to appendicectomy. Therefore 13 patients only had a DL. There were no complications in the MNA group of appendicetomies, although complications in the appendicitis group included ileus (1.6%, 2/120) and drainage of pelvic abscess (0.8%, 1/120). Histopathological diagnosis of appendicitis was confirmed in 99% of appendectomies (145/146). One patient had a macroscopically inflamed appendix removed that was normal. One patient who only had diagnostic laparoscopy was later diagnosed with inflammatory bowel disease. While 4 patients who underwent laparoscopy where re-admitted at least twice, and one patient four times during the follow-up period. However none underwent further laparoscopy. Conclusion: Although there has been some consensus that laparoscopic appendicectomy should be undertaken for the MNA, there has also been suggestion that this maybe associated with increased morbidity. We have shown that often at laparoscopy a macroscopically normal appendix histologically is acute appendicitis. There is no increase complication rate in this group. Furthermore future readmissions may be avoided in this group of female patients with RIF pain. Disclosure of interest: None Declared.